Radiation shielding study of heavy metal oxide bismuth-tungsten borate based glasses for defense and medical applications - Jaafar, Muhammad Fakhrul Naim; Abbas, Bashar Khudhair; Omar Baki, Sharudin; Mansor, Yaakob; Abdul Karim, Muhammad Khalis; Mahdi, Mohd Adzir (Semarak Ilmu Publishing, 2024)
n this work, series of bismuth-tungsten-borate oxide glasses: (90-x)B2O3-10WO3-xBi2O3, x= 5, 10, 15, 20, 25, were produced using conventional high temperature melt-quenching method. The obtained glasses show reduction in opacity and become denser as bismuth concentration increases. The molar volume also increases which may explain due to structural deformation of the glass matrix by the bismuth atoms once its concentration increases. In order to understand the bismuth effect on radiation shielding, we investigated the physical and ionizing shielding characteristics within energy range of 0.015 until 15 MeV. The mass attenuation coefficient (MAC), Half-Value-Layer (HVL) and Mean-Free-Path (MFP) parameters were fully explored throughout the study for photon shielding and advanced defense and medical applications.